Analysis Of Physical And Chemical Impact On The Krueng Montala River, Aceh Besar Regency: Sand And Stone Mining Activity Effect - Muhibbuddin, Muhibbuddin; Gani, Asri; Aulia, M Prayogie; Arahman*, Nasrul (Aceh International Journal of Science and Technology, 2023)
Rivers are important for human survival providing raw water for the community's clean water needs. Rivers also provide sand, gravel, and rocks commonly used for construction. However, improper exploitation of the river without considering environmental sustainability may cause future damage to it. The damage is usually caused by mining activities violating environmental regulations. The main point of this study is to evaluate the changes in the riverbank and riverbed of Krueng Montala River, Aceh, Indonesia, due to the mining activity around that place. The method used to analyze the changes was measuring the river's topographical contours at the end of mining activities and comparing the results with the initial licensing data based on the Mining License Number 540/DPMPTSP/414/IUP-OP/2020. Some of the equipment used in evaluating the condition of the river includes a Nikon Total Station, standard measuring tanks, Garmin 62Csx, and GPS. The measured data was also compared to the Technical Recommendation Number SA.02.03/BWS1/1542 from the River Basin Office of Sumatera 1. Based on the technical recommendation, the sufficient excavation volume is 10,201.44 m3 . The field data for lost and excavated materials at the research location was 40,861.4 m3 , and the total riverbank material loss at the study location was 7,566.33 m3 . The impact of mining activities on chemical parameters in the Krueng Montala River is still within the standard limits permitted by the government, such as TDS, TSS, COD, and BOD parameters. The influence of mining activities on chemical parameters in the Krueng Montala River did not show results that exceeded the standard limits permitted by the government, such as TDS, TSS, COD, and BOD parameters.